Perkembangan Bahasa dan Seni Siswa Kelas Tinggi Madrasah Ibtidaiyah Negeri I Yogyakarta - Muhamad Rofi Fauzi; Salmadina Saktiani (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The development experienced by humans when explored deeply will make people more confident in the power of God. Simple things such as the process of developing the language and art of children, in fact there is something extraordinary in it, which if disturbed will have an impact on further developments or other aspects.Writing this journal uses a qualitative approach, through observation, interviews, and documentation as a data collection technique. Based on the results of the research conducted, there are some results, namely the indicator of language development of VA class children basically has been achieved in accordance with the task of development at his age. But there are some things that have not been maximized in achieving this, such as the use of synonyms from several words, and metaphorical sentences that do not fully understand. The development of VA class art is in the phase of the Early Realism and the Early Age of Pseudo Naturalism which in the early realism phase In the period of Early Realism, children's work more closely resembled reality. Perspective awareness begins to emerge, but based on one's own vision. Keywords: Language Development, Art, Madrasah